The Implementation of Realistic Mathematics Education Approach to Improve Students' Mathematical Communication Ability in Statistics Course - Paroqi, Lois Lamya; Mursalin, Mursalin; Marhami, Marhami (Universitas Malikussaleh, 2020)
The purpose of this study is to analize the improving of mathematical communication skills’s students, the learning acktivities of student and student’s response at Realistic Mathematics (RME) learning. The research is held at MTs.S Syamsudduha in 2018-2019 years, which using quasi experiment with a quantitative approach. This study used two samples, they are experiment’s class as treatment class consists of 34 students and control’s class which not give the treatment consists of 36 students which the sample was taken in this research used the technique sampling purposive. This data was obtained with test technique and observation sheet. Data is analyzed with t test using SPSS 18, the result show that there is an increasing of mathematical communication skills of student on statistical study with the Realistic Mathematics Education (RME) learning. This shows that value of n-gain on student’s mathematical communication skill for experiment’s class is 0,49 and control’s class is 0,17 with significant 0,000 < 0,05, thats mean there is an increasing in the learning process. So, RME learning can improve student’s mathematical communication skills of students better than students who is taught by conventional learning.